Answer:
see explanation
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
(1)
Given m = - 2 and c = 2, then
y = - 2x + 2
(2)
Given m = [tex]\frac{1}{2}[/tex] and c = - 4, then
y = [tex]\frac{1}{2}[/tex] x - 4
(3)
Given m = - 1 and c = [tex]\frac{1}{2}[/tex], then
y = - x + [tex]\frac{1}{2}[/tex]
(4)
Given m = [tex]\frac{3}{4}[/tex] and c = - 5, then
y = [tex]\frac{3}{4}[/tex] x - 5
(5)
Given m = 5 and c = 1, then
y = 5x + 1
(6)
Given m = - [tex]\frac{2}{5}[/tex] and c = - 2, then
y = - [tex]\frac{2}{5}[/tex] x - 2